Investigation of CTNNB1 gene mutations and expression in hepatocellular carcinoma and cirrhosis in association with hepatitis B virus infection - Javanmard, Davod; Najafi, Mohammad; Babaei, Mohammad Reza; Karbalaie Niya, Mohammad Hadi; Esghaei, Maryam; Panahi, Mahshid; Safarnezhad Tameshkel, Fahimeh; Tavakoli, Ahmad; Jazayeri, Seyed Mohammad; Ghaffari, Hadi; Ataei-Pirkooh, Angila; Monavari, Seyed Hamidreaz; et al. (Infectious agents and cancer, 2020)
Hepatitis B virus (HBV), along with Hepatitis C virus chronic infection, represents a major risk factor for hepatocellular carcinoma (HCC) development. However, molecular mechanisms involved in the development of HCC are not yet completely understood. Recent studies have indicated that mutations in CTNNB1 gene encoding for β-catenin protein lead to aberrant activation of the Wnt/ β-catenin pathway. The mutations in turn activate several downstream genes, including c-Myc , promoting the neoplastic process. The present study evaluated the mutational profile of the CTNNB1 gene and expression levels of CTNNB1 and c-Myc genes in HBV-related HCC, as well as in cirrhotic and control tissues. Mutational analysis of the β-catenin gene and HBV genotyping were conducted by direct sequencing. Expression of β-catenin and c-Myc genes was assessed using real-time PCR. Among the HCC cases, 18.1% showed missense point mutation in exon 3 of CTNNB1 , more frequently in codons 32, 33, 38 and 45. The frequency of mutation in the hotspots of exon 3 was significantly higher in non-viral HCCs (29.4%) rather than HBV-related cases (12.7%, P = 0.021). The expression of β-catenin and c-Myc genes was found upregulated in cirrhotic tissues in association with HBV infection. Mutations at both phosphorylation and neighboring sites were associated with increased activity of the Wnt pathway. The results demonstrated that mutated β-catenin caused activation of the Wnt pathway, but the rate of CTNNB1 gene mutations was not related to HBV infection. HBV factors may deregulate the Wnt pathway by causing epigenetic alterations in the HBV-related HCC.